2015
DOI: 10.1177/1533034615573796
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic Models for Predicting Cervical Cancer Response to Radiation Therapy on Individual Basis Using Tumor Regression Measured In Vivo With Volumetric Imaging

Abstract: This article describes a macroscopic mathematical modeling approach to capture the interplay between solid tumor evolution and cell damage during radiotherapy. Volume regression profiles of 15 patients with uterine cervical cancer were reconstructed from serial cone-beam computed tomography data sets, acquired for image-guided radiotherapy, and used for model parameter learning by means of a genetic-based optimization. Patients, diagnosed with either squamous cell carcinoma or adenocarcinoma, underwent differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 42 publications
0
16
0
Order By: Relevance
“…First, regarding the potential increasing risk of second malignancies due to the low-dose irradiation of normal tissues [49]. Second, IMRT planning needs to take into consideration both organ motion and tumour regression, as several studies have reported on the inter-fraction and intra-fraction motions of the cervix [50][51][52][53][54][55]. In fact, Haripotepornkul et al [56] in their study concluded that daily image guidance and possibly re-planning of the treatment volumes are necessary to improve the accuracy of IMRT by accounting for the unpredictable changes in cervical position.…”
Section: Discussionmentioning
confidence: 99%
“…First, regarding the potential increasing risk of second malignancies due to the low-dose irradiation of normal tissues [49]. Second, IMRT planning needs to take into consideration both organ motion and tumour regression, as several studies have reported on the inter-fraction and intra-fraction motions of the cervix [50][51][52][53][54][55]. In fact, Haripotepornkul et al [56] in their study concluded that daily image guidance and possibly re-planning of the treatment volumes are necessary to improve the accuracy of IMRT by accounting for the unpredictable changes in cervical position.…”
Section: Discussionmentioning
confidence: 99%
“…It reflects the cell-line-specific growth rate and, possibly, environmental factors influencing the cell-cycle and tumor aggressiveness. The radiation therapy effects are usually modeled by means of the linear-quadratic (LQ) model, instead 23,31 . It defines the surviving fraction )(SF as trueSF=eαd1dα/β, where d is the delivered dose and the tumor radio-sensitivity is represented by the α (Gy −1 ) and β (Gy −2 ) parameters accounting for double (lethal) and single (possibly reparable) strand break damage to DNA, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…(1)–(3b)]. Similarly to our previous work, 23,26 the free parameters ( T d , α , and T 1/2 ) were optimized on an animal-specific basis by means of a custom genetic algorithm in order to achieve the best total volume fitting (∀ t , V)(tVv)(t+Vn)(t). In the parameter learning, T d , T 1/2 , and α were bounded in the range 3–7 days, 1–60 days, and 0.005–0.5 Gy −1 , respectively, according to the prior literature 22,33 .…”
Section: Methodsmentioning
confidence: 99%
“…Recent studies have demonstrated that 70% of cancer patients require adjuvant radiotherapy during their treatment course (3,4). For specific tumor types, including nasopharyngeal, esophageal and prostate cancer tumors, radiotherapy may even replace surgical treatment (3).…”
Section: Introductionmentioning
confidence: 99%
“…However, for specific cases of advanced or metastasized tumors with low radiosensitivity, the increased dose of radiation required may damage the surrounding healthy tissues and organs (3). Therefore, the identification of novel methods to enhance tumor cell radiosensitivity has become a recent focus of medical radiation research (4).…”
Section: Introductionmentioning
confidence: 99%